TEACHING READING COMPREHENSION IN NEWS ITEM TEXT BY USING FACTS QUESTIONS RESPONSES STRATEGY - Retna Handayani (Edukasi, 2017)
The objectives of this study were to find out whether or not there was a significant improvement on the tenth grade students’ news item reading before and after the treatment and to find out whether or not there was a significant difference on the tenth grade students’ news item reading between those who were taught by using Facts Questions Responses strategy and those who were. This study used pretest-posttest non-equivalent group design. The sample of the study was selected by using convenience sampling method. There were 70 students taken as sample. In collecting the data, test was used. The test was given twice to both experimental and control groups as a pretest and posttest. To verify the hypotheses, the score data between pretest and posttest in experimental groups were analyzed by using paired sample t-test. In paired sample t-test, the level of significance was 0.000 which was lower than 0.05 and t-value 8.304 was higher than t-table with df=34 (2.032). Then, the score data between posttest in experimental and control groups were analyzed by using independent sample t-test. In independent sample t-test, the level of significance was 0.028 which was lower than 0.05 and the t-value 2.243 which was higher than t-table with df =68 (1.995). It means that teaching reading comprehension in news item text by using FQR strategy had significant effect on the students’ reading comprehension achievement.